Alomorf Bahasa Loinang - Djindan, Nabillah (Kajian Linguistik, 2015)
Loinang languageis one of the languages which has not been researched, especially in Baloa Dodavillage, Pagimana sub-district, Banggai district, Central Sulawesi Province.This research focused on identifying the form of allomorph and analyzing theformation rule of allomorph in Loinang Language. The methode usedin this research is descriptive qualitative methode. The results showed that Loinang language consists of boundmorphemes such as prefix, suffix,infix, and confix. Each numbered 30 prefixes, 3 infixes, 3 suffixes, and, 13confixes as 49 pieces total affixes. Rules of formation of the appearance ofallomorph in Loinang language determined through the process of word formationor morphological processes, namely by affixation which form the class ofgrammatical categories of nouns, verbs, and adjectives. Allomorph found anappearance in a Loinang language, such as the morpheme members of paN- willmeet with the initial phonemes basic words /p/, /i/, /t/, /s/ to the variationsof allomorph pan-, pam-, paÎ·-, morpheme members of poN- will meet with theinitial phonemes basic word /p/, /b/, /k/, /l/, /u/, /a/ to the variations ofallomorph po-, pom-, pompa-, pompo-, ponaÎ·-, pon-, poÎ·-, morpheme members ofpiN- will meet with the initial phonemes basic words /h/, /s/, /l/, /k/, /p/,/m/, /a/ to the variations of allomorph pi-, pin-, pino-, pinaha-, pinoko-,pinom-, pinompo-, pinoÎ·-, morpheme members of tiN- will meet with the initialphonemes basic words /l/, /d/, /b/, /k/ to the variations of allomorph tina-,tinala-, tino-, tinom-, tinoÎ·-, morpheme members of iN- will meet with theinitial phonemes basic words /h/, /l/, /i/, /o/ to the variations of allomorphi-, iÎ·-, morpheme members of Mon- will meet with the initial phonemes basicwords /h/, /l/, /b/, /k/, /j/, /s/, /t/, /a/, /i/, /o/ to the variations ofallomorph mo-, mom-, mompo-, moÎ·-, mon-, the form of allomorph -um- will meetonly with the basic word phonemes /t/ - /i/, /p/ - /u/, /g/ - /Ô‘/, /t/ - /u/,/t/ - /i/, the form of allomorph -in- will only be met with the phonemes /p/ -/Ô‘/, /t/ - /o/, /t/ - /a/, /t/ - /i/, /s/ - /u/, the form of allomorph -am-only be met with the phonemes /p/ - /a/, /m/ - /i/, /b/ - /a/, /p/ - /i/, /m/ -/Ô‘/, the form of allomorph -mo will meet with the last phonemes basic words/i/, /a/, /s/, /É/, /n/, the form of allomorph -akon will meet with the lastphonemes basic words /Î·/, /m/, /o/, /u/, and the form of allomorph -i will meetwith the last phonemes basic words /Î·/,/m/,/s/.Â Keywords : Allomorph, Loinang, Generative